GAYA BAHASA DALAM KUMPULAN PUISI MEMBACA LAUT KARYA GUNTA WIRAWAN (KAJIAN STILISTIKA) - Nur Atika; Eti Sunarsih; Zulfahita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the use of language style in the poetry collection Reading the Sea by Gunta Wirawan which creates an aesthetic effect on the poem. This study aims to describe the language style of comparasion, opposition, linkage, and repetition in the poetry collection Reading the Sea by Gunta Wirawan. This study uses a descriptive method, qualitative research forms, and a stylistic approach. The data source in this study is the poetry collection Reading the Sea by Gunta Wirawan. Based on the results of the analysis, comparative language style data obtained, namely 32 data similes, 41 data metaphors, 51 data personifications, 2 data depersonifications, 21 data allegories, 3 data antithesis, 6 data pleonasm or tautulogy, 5 data perifrasis, and 2 data correction or epanortosis. The language syle of opposition is hyperbole 46 data, litotes 5 data, irony 4 data, oxymoron 1 data, zeugma 1 data, satire 7 data, inuendo 1 data, paradox 3 data, climax 3 data, anticlimax 2 data, and apostrophe 6 data. The language style of linkage is metonymy 21 data, synecdoche 20 data, allusion 1 data, euphemism 5 data, eponym 2 data, epithet 1 data, antonomasia 4 data, erotesis 18 data, parallelism 2 data, ellipsis 5 data, asydenton 6 data, and polysyndeton 16 data. And the repetition language style is alliteration 22 data, assonance 15 data, epizeukis 10 data, anaphora 18 data, epistrofa 1 data, mesodiplosis 5 data, and anadiplosis 1 data. The results of this study are planned to be implemented in the Indonesian Language teaching module for Junior High School Level Phase D class VIII semester 2 with Learning Objective Flow 5.1 students can recognize the meaning and characteristics of poetry and identify the elements that build poetry.